Divide and Conquer Methods for Solving Linear Systems - Mezzar, Youssouf; Belghaba, Kacem (Communications in Mathematics and Applications, 2023)
The Divide and Conquer (D&C) strategy solves a problem by breaking it down into subproblems, which are themselves smaller cases of the same type of problem. We will see how this technique creates a numerical recursive algorithm to calculate the inverse of square matrices and solve linear systems using Schur’s complement, Cholesky, and LU decomposition.